2016
DOI: 10.3892/etm.2016.3246
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes in gap junctional intercellular communication in a rat model of overactive bladder syndrome induced by partial bladder outlet obstruction

Abstract: The aim of the present study was to investigate the association between connexin (Cx)43 levels and alterations in gap junctional mediation of intercellular communication in overactive bladder syndrome (OAB), and to examine the effects of connexin inhibitor on this condition. Adult female Wistar rats with OAB following partial bladder outlet obstruction (PBBO) (OAB group, n=37) and sham-operated rats (control group, n=17) were studied. The ultrastructure of the rat detrusor was observed by transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…36 High levels of gap junction expression would likewise be expected to make the bladder smooth muscle cells hypersensitive to cholinergic stimulation, presumably due to excessive diffusion of Ca 2+ ions among detrusor coupled myocytes. 15,[37][38][39] Indeed, upregulation of connexin 43, a predominant connexin protein expressed in human bladder gap junctions, has been identified in patients with urgency incontinence. 32 The use of gene therapy to treat bladder dysfunction may have intrinsic advantages over conventional pharmacotherapies when the therapeutic target is subject to epigenetic modification.…”
Section: Bk Channel Function and Channelopathymentioning
confidence: 99%
“…36 High levels of gap junction expression would likewise be expected to make the bladder smooth muscle cells hypersensitive to cholinergic stimulation, presumably due to excessive diffusion of Ca 2+ ions among detrusor coupled myocytes. 15,[37][38][39] Indeed, upregulation of connexin 43, a predominant connexin protein expressed in human bladder gap junctions, has been identified in patients with urgency incontinence. 32 The use of gene therapy to treat bladder dysfunction may have intrinsic advantages over conventional pharmacotherapies when the therapeutic target is subject to epigenetic modification.…”
Section: Bk Channel Function and Channelopathymentioning
confidence: 99%
“…Several studies have shown the mechanisms of gap junctional communication in the pBOO model . Upregulation of connexin 43 induces structural and functional changes after pBOO, so connexin inhibitors could be a novel therapeutic option for the treatment of OAB …”
Section: Morphologymentioning
confidence: 99%
“…Furthermore, pBOO upregulated the Rho‐associated kinase pathway . Upregulation of connexin 43 induces structural and functional alterations in gap junctional intercellular communication following pBOO . pBOO also changes immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling between ICs, the urothelium, and detrusor smooth muscle cells is another important issue which determines the normal function of the bladder and is significantly altered in disease, as demonstrated in BOO [11][12][13][14][15][16], OAB [17,18], and IC/BPS [19]. Furthermore, cell culture studies showed that cytokines can control connexin (Cx)43 and Cx45 expression in bladder smooth muscle cells and interstitial cells [20][21][22].…”
Section: Introductionmentioning
confidence: 99%